Perspectives: Neonatal acute kidney injury (AKI) in low and middle income countries (LMIC) - McCulloch, Mignon I.; Adabayeri, Victoria M.; Goka, Selasie; Khumalo, Tholang S.; Lala, Nilesh; Leahy, Shannon; Ngubane-Mwandla, Nokukhanya; Nourse, Peter J.; Nyann, Beatrice I.; Petersen, Karen L.; Levy, Cecil S. (Frontiers in Pediatrics, 2022)
Neonatal AKI remains a challenge in Low and Middle Income Countries(LMIC). In this perspective we address issues of diagnosis and risk factors particular to less well resourced regions. The conservative management pre-kidney replacement therapy(pre-KRT) is prioritised and challenges of KRT are described. Special emphasis is placed on ethical and palliation principles.